Trust and Convenience Drive E-Money Adoption Among Students in Indonesia: Kepercayaan dan Kenyamanan Mendorong Adopsi E-Money di Kalangan Pelajar di Indonesia - Putra, Bisma Akbar Wahyu Tri; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how perceived usefulness, convenience, service features, and trust influence Umsida students' decisions to use